Epidemiological patterns of skin cancer among patients presenting to the department of radiation oncology at Charlotte Maxeke Johannesburg Academic Hospital between 2006 – 2011 - Muya, Sikudhani (My University, 2020)
Purpose To describe the epidemiological pattern of skin cancer among patients attending the Department of radiation oncology at Charlotte Maxeke Johannesburg Academic Hospital between 2006-2011. Method and materials 207 patients with histologically diagnosed non melanoma skin cancer from January 2006 – December 2011 were retrospectively reviewed and analysed using SPSS. Trends in incidence of non melanoma skin cancers by race, age, gender, stage, and anatomical distribution in albino and general population were analyzed. Results Of the 207 patients analysed, 67.6 % (140) were males and 32.4 % (67) were females, there was no association between histology and gender. White Population constituted 60.4% (125) of all the patients analysed, followed by black (combination of Blacks, Coloured, and Indians as the number of coloured and Indians was too small only 2 patients) population 39.6 % (82). Squamous cell carcinoma was the most common histology found in blacks 92.6% (75 patients) while most whites had basal cell carcinoma 54.8 % (69 patients) and the difference was statistically significant. The mean age at diagnosis was 61.3 years. The mean age for blacks was 52.96 years (52.96 ±15.8 years) and that for whites was 66.79 years (66.79 ±13.56 years). There was an association between histology and age. The majority of whites presented with early stages of disease (stage 1 and 2) 88.0% (110 patients) while blacks presented with late stages of disease (stage 3 and 4) 46.3% (38 patients). Head and neck was the most common site of lesions 65.2% (135 patients) for both whites and blacks but was more common in whites 72.8% (91 patients) while blacks had 53.7% (44 patients). Leg lesions were more common in blacks 30.5% (25 patients) and very few whites had leg lesions 8.0% (10 patients) and chest lesions 16% (35 lesions). There was an association between histology, race and anatomical distribution of non melanoma skin cancer. Albino accounted for about 47.5 % (38 patients) of the black population with SCC being the commonest histology 29.5% (36 patients) followed by basal cell carcinoma 2.7% (2 patients), there was no association between albinism and stage of the disease and most of the lesions were on the head and neck region but there was no difference in the anatomical distribution of skin lesions between albinos and normal black population. Conclusion SCC is the most common histology of non melanoma skin cancer and more common in blacks than whites. BCC is the second most seen in whites, and the most frequently seen subtype was nodular BCC. Most whites presented with early stages of disease compared to blacks. There was an association between histology and age as well as race and anatomical distribution of lesions. There was no association between histology and gender. Albinos present with SCC commonly than BCC with more lesions found on the head and neck. The findings are similar and comparable to most of the studies done in other parts of the world. Prospective epidemiological studies are suggested in collaboration with dermatologists and plastic surgeons as most of the skin cancer patients are seen by them before referral to Radiation Oncologists.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Medicine to the Faculty of Health Science, University of the Witwatersrand, Johannesburg, 2020